2019
DOI: 10.17941/agd.708506
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of use of food and vegetable products in the adults having digestive system problems

Abstract: Giriş ve Amaç: Bu çalışma yetişkin bireylerin sindirim sistemi problemlerinde kullandıkları besin ve bitkisel ürünleri saptamak amacıyla gerçekleştirilmiştir. Gereç ve Yöntem: Araştırma örneklemi, Aralık 2017-Mart 2018 tarihleri arasında Mersin ilinde bulunan bir devlet hastanesine herhangi bir nedenle başvurmuş, aynı hastanede görevli hekimler tarafından ilaç reçeteleri düzenlenmiş ve ilaç reçetelerini temin etmek amacıyla bir eczaneye gelmiş olan 18-80 yaş arası 196 yetişkin bireyden oluşmaktadır. Çalışmada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…24 In another study of 196 adults with digestive system problems, 53.8% reported that they used diet and herbal products for these GIS problems. 25 In a study in Sweden, 1029 patients presenting at the emergency department were questioned about their use of alternative medicine. It was determined that 72.9% of the patients applied alternative medicine at some time in their lives, and the middle-aged female group with a middle-school level of education, and those who used drugs without a prescription used alternative medicine more.…”
Section: Discussionmentioning
confidence: 99%
“…24 In another study of 196 adults with digestive system problems, 53.8% reported that they used diet and herbal products for these GIS problems. 25 In a study in Sweden, 1029 patients presenting at the emergency department were questioned about their use of alternative medicine. It was determined that 72.9% of the patients applied alternative medicine at some time in their lives, and the middle-aged female group with a middle-school level of education, and those who used drugs without a prescription used alternative medicine more.…”
Section: Discussionmentioning
confidence: 99%
“…Bu tedavi sistemlerinin uygulamalarında ülkelerin coğrafi konumlarına, etnik kökenlerine, eğitim durumlarına, sosyoekonomik faktörlerine ve dinî inanışlarına göre değişiklikler görülmektedir. 5 Bu araştırma, 2020-2021 yılları arasında Ardahan, Iğdır ve Kars illeri ve çevresinde yaşayan insanların SS hastalıklarında kullandıkları tıbbi bitkilerin kısımlarını ve hazırlama yöntemlerini belgelemek amacıyla yapılmıştır.…”
unclassified